Carotenoid pigments of red, green and brown macroalgae species as potential active pharmaceutical ingredients - Othman, Rashidi; Md Amin, Nur Alifah; Abu Bakar, Ainaa Eliah; Ahmad Fadzillah, Nurrulhidayah; Mahmad, Noraini (SET Publisher, 2019)
Active Pharmaceutical Ingredient (API) is a substance used in a finished pharmaceutical product, intended to furnish pharmacological activity or contribute direct effect in the diagnosis, cure, mitigation, treatment or prevention of disease. It also provides a direct effect in restoring, correcting or modifying physiological functions in human beings. Macroalgae, also known as seaweed, are plant-like organisms that can be found in a marine habitat. Macroalgae has been given huge concern because of its high nutritional value and short-term growth, which is only 45 days per cycle. Therefore, three red macroalgae species of Eucheuma denticulatum, Gracilaria tikvahiae and Kappaphycus striatum), as well as green and brown macroalgae species of Caulerpa lentillifera and Padina pavonica were selected to determine their carotenoids content and composition by using UV-Vis spectrophotometer and HPLC analysis. The main carotenoids identified in red, green and brown macroalgae species were zeaxanthin, lutein, β-carotene and violaxanthin. Marked differences were observed between red, green and brown macroalgae carotenoids content and composition. Zeaxanthin and β-carotene were detected in all red, green and brown macroalgae ranged from 3.61 to 21.30 μg/g DW and 2.44 to 10.70 μg/g DW respectively. Violaxanthin was found only in green macroalgae (8.93 μg/g DW) whereas lutein was found only in red macroalgae (9.57 to 38.60 μg/g DW). In terms of total carotenoid content, green macroalgae contained the highest amount of carotenoid (100.89 ± 14.71 μg/g DW). The significant outcome of the research will be new natural carotenoid pigment sources as potential active pharmaceutical ingredients which can be beneficial to halal health-promoting products industry.